DEVELOPMENT OF LEARNING MEDIA ASSISTED BY GOOGLE SITES WITH AN INDUCTIVE APPROACH ON DYNAMIC FLUIDS MATERIAL: PENGEMBANGAN MEDIA PEMBELAJARAN BERBANTUAN GOOGLE SITES DENGAN PENDEKATAN INDUKTIF PADA MATERI FLUIDA DINAMIS - Agung Heka P; Anggara Budi Susila; Dwi Susanti (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2025)
This research is developed because development of technological advancements in educational learning and aims to develop learning media that can assist students in understanding in dynamic fluid subject, and the feasibility of learning through Google Sites. This research used Borg & Gall development model, consisting of several stages: research and data collection, planning, development of product drafts, field trials, refinement of field trial products, field implementation trials, refinement of operational product, operational field trials, refinement of final products, dissemination, and implementation. In the development stage, three validators were media experts, subject matter experts, and learning experts to assess the feasibility of the media, materials, and learning in this study. This research is applied to high school students on dynamic fluid learning materials and uses an inductive approach in delivering the material. Based on the analysis of the needs of eleventh-grade high schoolstudents and filled out by 29 respondents, it was found that 86.2% do not have difficulty using a laptop/computer/smartphone during learning activities, and 86.2% answered that learning dynamic fluid materials could be better understood when using learning media assisted by Google Sites. This research is expected to become suitable learning media for use by students or teachers.